2003
DOI: 10.1001/archpsyc.60.5.517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Trichotillomania With Behavioral Therapy or Fluoxetine

Abstract: Behavioral therapy is highly effective for reducing symptoms of trichotillomania in the short term, whereas fluoxetine is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
122
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 26 publications
7
122
0
13
Order By: Relevance
“…Van Minnen et al 135 conduziram um estudo randomizado comparando TC e fluoxetina com lista de espera. Completaram as 12 semanas propostas com 40 pacientes; destes, 14 fizeram TC, 11 receberam fluoxetina (60 mg/d) e 15 eram de lista de espera (grupo controle).…”
Section: Tratamento Farmacológicounclassified
See 2 more Smart Citations
“…Van Minnen et al 135 conduziram um estudo randomizado comparando TC e fluoxetina com lista de espera. Completaram as 12 semanas propostas com 40 pacientes; destes, 14 fizeram TC, 11 receberam fluoxetina (60 mg/d) e 15 eram de lista de espera (grupo controle).…”
Section: Tratamento Farmacológicounclassified
“…Completaram as 12 semanas propostas com 40 pacientes; destes, 14 fizeram TC, 11 receberam fluoxetina (60 mg/d) e 15 eram de lista de espera (grupo controle). Os resultados sugerem que a TC foi superior à fluoxetina e ao grupo controle 135 .…”
Section: Tratamento Farmacológicounclassified
See 1 more Smart Citation
“…Both are characterized by difficulties suppressing inappropriate repetitive behaviors, suggesting underlying dysregulation in inhibitory control processes [9]. Case series, double blind studies demonstrated the effectiveness of the SSRI treatment in TTM [10][11][12][13]. Short-term treatment with SSRI's was effective in most cases, however in the long term follow up three major problems occurred [1].…”
Section: Introductionmentioning
confidence: 99%
“…The early onset form tends to remit more readily, but the late onset form, occurring after age 13, often becomes chronic. Behaviour therapy as in obsessive compulsive disorder is particularly effective [3]. Serotonergic agents such as fluoxetine can also be used in the treatment.…”
mentioning
confidence: 99%